Droplet epitaxy growth of telecom InAs quantum dots on metamorphic InAlAs/GaAs(111)A. (18th February 2015) - Ha, Neul; Mano, Takaaki; Kuroda, Takashi; Mitsuishi, Kazutaka; Ohtake, Akihiro; Castellano, Andrea; Sanguinetti, Stefano; Noda, Takeshi; Sakuma, Yoshiki; Sakoda, Kazuaki
Abstract: We demonstrated the droplet epitaxial growth of InAs quantum dots on a GaAs(111)A substrate, which emitted at telecommunication wavelengths. A high-quality metamorphic In0.52 Al0.48 As layer was formed by inserting three monolayers of InAs between GaAs(111)A and InAlAs. InAs quantum dots were grown on the InAlAs surface by droplet epitaxy. They exhibited a laterally symmetrical shape owing to the C 3 v symmetry of the {111} surface. The photoluminescence signals of capped quantum dots indicated broadband spectra covering wavelengths from 1.3 to 1.55 µm. Thus, our dots are potentially useful for constructing entangled photon sources compatible with current telecommunication networks.